Bacteriological profile and its antibiotic sensitivity in UTI patients in hospitals and diagnostic centers in Bangladesh - Nahar, Noshin (Brac University, 2022)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2021.